The Corporation of Foreign Bondholders - Mauro, Paolo (International Monetary Fund, 2003)
This paper analyzes the Corporation of Foreign Bondholders (CFB), an association of British investors holding bonds issued by foreign governments. The CFB played a key role during the heyday of international bond finance, 1870-1913, and in the aftermath of the defaults of the 1930s. It fostered coordination among creditors, especially in cases of default, arranging successfully for many important debt restructurings, though failing persistently in a few cases. While a revamped creditor association might once again help facilitate creditor coordination, the relative appeal of defection over coordination is greater today than it was in the past. The CFB may have had an easier time than any comparable body would have today